KRITIK ILMIAH DALAM PERSPEKTIF ISLAM - Muh Taqdir Nur (Jurnal Dakwah Tabligh, 2015)
In Islam, if you want to gain the world and the hereafter, then let the science. Quite the reverse, use of science and technology geared to specific interests, descriptive and endangering humanity. it is very necessary to build an awareness that science and technology as part of the verses of Allah and a mandate that can not be separated from the responsibility of the creator of the science. With this awareness will bring a commitment to address all forms of science and technology in the area thought that in accordance with Islamic teachings. One key to success is the enthusiasm of Islamic scholarship and counter criticism among Islamic scholars. Of course, criticizing spirit is indispensable for the progress and development of science anywhere. Utilization of science and technology geared to specific interests, descriptive and endangering humanity. Scientific criticism not just throw the spotlight, as a statement of dissatisfaction or stuck on the territory of like or dislike, but must be based on some ethics.